Pengaruh Influencer TikTok Terhadap Brand Awareness Produk Somethinc Pada Generasi Z Dengan Interaktivitas Pengguna Sebagai Variabel Mediasi - Anne Zahratussa’adah; Aditia abdurachman; Rina madyasari; Alfin nur arifah (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2026)
This study aims to analyze the influence of TikTok influencers on brand awareness of Somethinc products among Generation Z in Indonesia, with user interactivity as a mediating variable. This research is motivated by the suboptimal brand awareness of Somethinc despite utilizing TikTok influencers as a digital marketing strategy. Furthermore, previous research on the influence of influencer marketing on brand awareness has shown mixed results, while studies on the role of user interactivity as a mediating variable are still limited. The novelty of this study lies in examining user interactivity in explaining the relationship between TikTok influencers and brand awareness of local skincare products. The study used a quantitative approach involving 135 Generation Z TikTok users in Indonesia. The results showed that TikTok influencers positively influence user interactivity and brand awareness. User interactivity also positively influences brand awareness and partially mediates the relationship. These findings suggest that Somethinc needs to optimize interactive campaigns and user-generated content to increase brand awareness.